The Effect of Health Education about Back Massage on the Level of Knowledge in Adapting Labor Pain - Neneng Safitri; Karmita Sari; Rena Oki Alestari; Ivana Devitasari (Health and Technology Journal (HTechJ), 2025)
Labor pain is a physiological phenomenon experienced by every pregnant woman. However, the response to this pain varies greatly, from screaming and crying to getting angry. One non-pharmacological method that can be used to reduce labor pain is back massage. This technique involves applying pressure to soft tissue, such as muscles, tendons, or ligaments, without causing joint movement. Massage not only relieves pain but also increases relaxation and improves blood circulation. However, an initial Bukit Hindu Palangka Raya Community Health Center survey showed that most pregnant women did not understand this technique. Therefore, this study aims to evaluate the effect of health education regarding back massage techniques on the level of knowledge of pregnant women in adapting to labor pain. This research uses a pre-experimental design with a "one-group pre-test and post-test design" approach. Sampling was carried out by purposive sampling with 30 pregnant women as respondents. Data were analyzed using the Wilcoxon statistical test to assess differences in knowledge levels before and after intervention. The results of statistical analysis show a significance value < p-value (0.000 < 0.05), which means the alternative hypothesis (Ha) is accepted. This shows that health education about back massage techniques has a significant influence on increasing the level of knowledge of pregnant women in adapting to labor pain. This research proves that health education effectively increases pregnant women's understanding of back massage techniques. This method can be a non-pharmacological solution to reduce labor pain. It is hoped that health workers can be more proactive in educating pregnant women through direct discussions or visual media such as flipcharts. Health education about back massage techniques has been proven to increase pregnant women's knowledge in adapting to labor pain. Implementing this kind of counseling routinely in health facilities is important to support the mother's comfort during birthing.